DIPLOMASI INDONESIA DALAM MEMPROMOSIKAN PACU JALUR KUANTAN SINGINGI SEBAGAI DESTINASI PARIWISATA INTERNASIONAL - Aisyah, Siti; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research analyzes Indonesia's diplomacy in promoting the Pacu Jalur festival in Kuantan Singingi as an international tourism destination. The tourism potential of Pacu Jalur in Kuantan Singingi is significant as it has been named one of the top 10 Karisma Event Nusantara (KEN) by the Ministry of Tourism and Creative Economy of the Republic of Indonesia. Pacu Jalur has also been designated by UNESCO as an Intangible Cultural Heritage since 2014 in the category of